A multimodal approach prevents instability after total hip arthroplasty: A 1 year follow-up prospective study (2018)
Introduction: Joint dislocation is one of the most frequent complications after hip arthroplasty. Multiple strategies have demonstrated ability to prevent instability when used in isolation, but the effect when more than one intervention is implemented has not been measured. The purpose of this study is to assess the rate of dislocation after implementation of a protocol of combined strategies for prevention of instability. Materials and methods: Consecutive patients undergoing primary total hip replacement for hip osteoarthritis between February 2012 and June 2014 were included. A multimodal protocol including patient education, use of large femoral heads, posterior soft-tissue repair, and intraoperative adjustment of limb length and hip offset was applied. Dislocation episodes were documented trough medical records review and a telephonic follow-up at 3 and 12 months after surgery. Results: During the period of study 331 patients were included, mean age was 66 years and 68.8% were females. Only 0.91% of patients were lost to follow-up. Eighty-nine percent of patients received all interventions. Cumulative dislocation rate at 3 months was 0.60% and 0.90% at 12 months. Conclusions: The implementation of a multimodal protocol for prevention of prosthesis instability produces a low rate of dislocation, which compares favorably with benchmarks. We recommend the use of a combination of multiple interventions to prevent this complication. © 2016